r 2022
DOI: 10.20955/r.104.78-91
|View full text |Cite
|
Sign up to set email alerts
|

Global Supply Chain Disruptions and Inflation During the COVID-19 Pandemic

Abstract: The COVID-19-pandemic recession and recovery have been unique compared with previous recessions, largely due to policies that led to behavioral changes. Lockdowns meant people were traveling less both for work and for leisure, eating out less, and going to fewer entertainment venues, among other things. At the same time, work from home and fiscal stimulus packages increased the demand for certain goods such as technological goods, cars, and furniture. These changes resulted in an overall shift away from consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…Moreover, inflation in many developed countries has reached levels not seen in decades. Of course, on top of the effects of the fiscal boosts, there are other reasons behind this elevated inflation readings, such as disruptions to supply chains (Santacreu and LaBelle, 2022) and, more recently, the war in Ukraine (Caldara et al, 2022). Meanwhile, the labor market upheaval brought upon by pandemic lockdowns has largely been resolved.…”
Section: The Feedback Of Inflation To Wagesmentioning
confidence: 99%
“…Moreover, inflation in many developed countries has reached levels not seen in decades. Of course, on top of the effects of the fiscal boosts, there are other reasons behind this elevated inflation readings, such as disruptions to supply chains (Santacreu and LaBelle, 2022) and, more recently, the war in Ukraine (Caldara et al, 2022). Meanwhile, the labor market upheaval brought upon by pandemic lockdowns has largely been resolved.…”
Section: The Feedback Of Inflation To Wagesmentioning
confidence: 99%
“…Several recent papers have studied the effect of COVID in the presence of global production networks (Cakmakli et al, 2021;Bonadio et al, 2021) but do not consider the supply constraints related to the time to restock that we emphasize. Another literature considers, empirically, how cross-industry delays or backlogs affect industry prices or production (Alessandria et al, 2022;Santacreu and LaBelle, 2022). Recently, Cavallo and Kryvtsov (2021) has shown that COVID has substantially and persistently increased the retail stock out rate in the U.S. and around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The volatility of supply chains and the prospect that these disruptions may remain elevated for a sustained period pose a significant challenge for monetary policymakers. There is growing evidence that supply chain disruptions have contributed to the recent increase in global inflation (e.g., Benigno et al 2022;LaBelle and Santacreu 2022;Finck and Tillmann 2022). One concern is that this effect could become entrenched, leading to expectations of permanently higher inflation that in turn could spill over into higher wage demands and higher prices for non-tradable goods and services.…”
Section: Appendices 1 Introductionmentioning
confidence: 99%